Engineering Biomimetic Materials for Islet Transplantation - Y. Yang, Ethan; P. Kronenfeld, Joshua; L. Stabler, Cherie (Current Diabetes Reviews, 2015)
A closed-loop system that provides both the sensing of glucose and the appropriate dosage of insulin could dramatically improve treatment options for insulin-dependent diabetics. The intrahepatic implantation of allogeneic islets has the potential to provide this intimate control, by transplanting the very cells that have this inherent sensing and secretion capacity. Limiting islet transplantation, however, is the significant loss and dysfunction of islets following implantation, due to the poor engraftment environment and significant immunological attack. In this review, we outline approaches that seek to address these challenges via engineering biomimetic materials. These materials can serve to mimic natural processes that work toward improving engraftment, minimizing inflammation, and directing immunological responses. Biomimetic materials can serve to house cells, recapitulate native microenvironments, release therapeutic agents in a physiological manner, and/or present agents to direct cells towards desired responses. By integrating these approaches, superior platforms capable of improving long-term engraftment and acceptance of transplanted islets are on the horizon.
Keywords: anoikis